The Work of Community Gardens: Reclaiming Place for Community in the City. (February 2018) - Cumbers, Andrew; Shaw, Deirdre; Crossan, John; McMaster, Robert
The growth of community gardens has become the source of much academic debate regarding their role in community empowerment in the contemporary city. In this article, we focus upon the work being done in community gardens, using gardening in Glasgow as a case study. We argue that while community gardening cannot be divorced from more regressive underlying economic and social processes accompanying neoliberal austerity policies, it does provide space for important forms of work that address social needs and advance community empowerment. In developing this argument we use recent geographical scholarship concerning the generative role of place in bringing together individuals and communities in new collective forms of working. Community gardens are places that facilitate the recovery of individual agency, construction of new forms of knowledge and participation, and renewal of reflexive and proactive communities that provide broader lessons for building more progressive forms of work in cities.